2013
DOI: 10.1111/jsm.12152
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Correlates of Sexual Dysfunction in Female Rectal and Anal Cancer Survivors: Analysis of Baseline Intervention Data

Abstract: Introduction Sexual dysfunction represents a complex and multifactorial construct that can affect both men and women and has been noted to often deteriorate significantly after treatment for rectal and anal cancer. Despite this, it remains an understudied, underreported and undertreated issue in the field of cancer survivorship. Aim This study examined the characteristics of women enrolled in an intervention trial to treat sexual dysfunction, and explored the relationship between sexual functioning and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 61 publications
0
51
0
Order By: Relevance
“…We also found evidence of this in our qualitative data, where the ostomy appliance was described as “ugly” and “not appealing.” Evidence suggests that sexual dysfunction is associated with a range of psychological well-being outcomes, including body image, anxiety, and posttraumatic distress. 27,28 Survivors with permanent ostomies are also more likely to experience social distress post-treatment. 29 Similar to other studies 4,5 , we found a high prevalence of persistent sexual dysfunction associated symptoms in both female and male survivors regardless of ostomy status.…”
Section: Discussionmentioning
confidence: 99%
“…We also found evidence of this in our qualitative data, where the ostomy appliance was described as “ugly” and “not appealing.” Evidence suggests that sexual dysfunction is associated with a range of psychological well-being outcomes, including body image, anxiety, and posttraumatic distress. 27,28 Survivors with permanent ostomies are also more likely to experience social distress post-treatment. 29 Similar to other studies 4,5 , we found a high prevalence of persistent sexual dysfunction associated symptoms in both female and male survivors regardless of ostomy status.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also calculated these effect sizes excluding women who were not sexually active at baseline (see Table 2). Similar to prior studies [33, 34], women who left blank or indicated no sexual activity/ intercourse to ≥8 of the 15 FSFI questions with this response option were considered to have insufficient sexual activity for the FSFI to be a valid assessment of their functioning. This analysis of the subgroup of women considered sexually active at baseline was not a part of the original analysis plan in the protocol for this RCT; however, given that the validity of the FSFI as an outcome measure is contingent upon its use among sexually active respondents, we felt it important to present the effect sizes for this sexually active subgroup in order to provide the most appropriate effect size estimates for researchers planning similar studies that will utilize the FSFI.…”
Section: Methodsmentioning
confidence: 99%
“…Participants (N=70) were part of a sexual health intervention study for women reporting low to moderate satisfaction with their sexual functioning and overall sexual life (see Philip and colleagues [28] for full study information). Sexual satisfaction was assessed using an item from the Female Sexual Function Index (“Over the past 4 weeks, how satisfied have you been with your overall sexual life?”; 5=Very Satisfied to 1=Very Dissatisfied) and individuals scoring a 5 were excluded [29].…”
Section: Methodsmentioning
confidence: 99%